Dental Implants - Saadoon, Abdullah Saad; Dzodzuashvili, Grigol (Caucasus Journal of Health Sciences and Public Health, 2018)
Dental implants are metal posts or frames that are surgically positioned into the jawbone beneath your gums. Once in place, they allow your dentist to mount replacement teeth on to them. Because implants fuse to patient jawbone, they provide stable support for artificial teeth. Dentures and bridges mounted to implants won't slip or shift in the patient mouth , an especially important benefit when eating and speaking. This secure fit helps the dentures and bridges , as well as individual crowns placed over implants , feel more natural than conventional bridges or dentures. For some people, ordinary bridges and dentures are simply not comfortable or even possible, due to sore spots, poor ridges or gagging. In addition, ordinary bridges must be attached to teeth on either side of the space left by the missing tooth. An advantage of implants is that no adjacent teeth need to be prepared or ground down to hold your new replacement tooth/teeth in place. To receive implants, patients need to have healthy gums and adequate bone to support the implant. they must also commit to keeping these structures healthy. Meticulous oral hygiene and regular dental visits are critical to the long-term success of dental implants. The American Dental Association considers two types of implants to be safe. They are: Endosteal implants — these are surgically implanted directly into the jawbone. Once the surrounding gum tissue has healed, a second surgery is needed to connect a post to the original implant. Finally, an artificial tooth (or teeth) is attached to the post-individually, or grouped on a bridge or denture. Sub periosteal implants — these consist of a metal frame that is fitted onto the jawbone just below the gum tissue. As the gums heal, the frame becomes fixed to the jawbone. Posts, which are attached to the frame, protrude through the gums. As with endosteal implants, artificial teeth are then mounted to the posts.